Unified security model of authenticated key exchange with specific adversarial capabilities. Issue 1 (1st January 2016) - Wen, Weiqiang; Wang, Libin; Pan, Jiaxin
Abstract : The most widely accepted models in the security proofs of authenticated key exchange protocols are the Canetti–Krawczyk (CK) and extended CK models that admit different adversarial queries with ambiguities and incomparable strength. It is desirable to incorporate specific and powerful adversarial queries into a single unified security model and establish a more practical oriented security notion. Concerning the security of one‐round implicitly authenticated Diffie–Hellman (DH) key exchange protocols, the authors present a unified security model that has many advantages over the previous ones. In the model, a system environment is set up, all of adversarial queries are practically interpreted and definitely characterised through physical environment, and some rigorous rules of secret leakage are also specified. To demonstrate usability of their model, a new protocol based on the OAKE protocol is proposed, which satisfies the presented strong security notion and attains high efficiency. The protocol is proven secure in random oracle model under gap DH assumption.